Motherhood penalty for female physicians in Japan: evidence from a medical school's alumni data - Sachiyo Nishida; Emiko Usui; Takashi Oshio; Naoya Masumori; Kazufumi Tsuchihashi (BMC, 2024)
Abstract Background Female physicians with children often work fewer hours and take fewer shifts due to additional family responsibilities. This can contribute to a gender pay gap in the medical profession. However, limited research in Japan has quantitatively examined the factors contributing to this gap. This study aims to address this gap in the literature. Methods We analyzed the alumni data from a medical school in Hokkaido, Japan, for 260 physicians (198 males and 62 females). We used multivariable regression models to identify factors influencing earnings from medical practice, with a focus on gender, work schedules, parenthood, and any career interruptions related to childcare. Results Our analysis revealed a 25.0% earnings gap between male and female physicians. Nearly all female physicians with children experienced career interruptions due to childcare, while this was uncommon for male physicians. When these childcare-related interruptions were factored in, the gender pay gap narrowed by 9.7%. After adjusting for work schedules and specialty choices, female physicians with children still earned 37.2% less than male physicians, while those without children earned only 4.4% less. This suggests that motherhood is a significant driver of the gender pay gap among physicians. Conclusions These findings highlight the negative impact of motherhood on female physicians' earnings. This emphasizes the need for policy measures to mitigate the disadvantages faced by mothers in the medical profession.